Real‐Time Study on Structure Formation and the Intercalation Process of Polymer: Fullerene Bulk Heterojunction Thin Films. Issue 3 (6th March 2020) - Kassar, Thaer; Berlinghof, Marvin; Güldal, Nusret Sena; Schmutzler, Tilo; Zontone, Federico; Brandl, Marco; Metwalli, Ezzeldin; Will, Johannes; Li, Ning; Ameri, Tayebeh; Brabec, Christoph J.; Unruh, Tobias
Abstract : Fullerene Intercalation In article number 1900508, Tobias Unruh and co‐workers report on the formation process of a PC60BM:pBTTT‐C14 active layer of a bulk heterojunction organic photovoltaic solar cell during evaporation of the solvent:additive mixture. By careful evaluation of the in‐situ grazing incidence small‐angle X‐ray scattering measurements, a conclusive picture of the 5‐step mechanism of fullerene intercalation and additive‐tuned evolution of the nanoscopic film structure during the drying process could be obtained.